Cryptolaria crassa Fraser 1940 - Calder, Dale R.; Choong, Henry H. C. (Zenodo, 2018)
Diphasia crassa Fraser, 1940a Synthecium protectum Jäderholm, 1903: 290, pl. 13, figs. 5, 6. Diphasia crassa Fraser, 1940a: 579, pl. 33, figs. 8a, b. Synthecium crassum .— Vervoort & Watson, 2003: 246. Holotype. USNM 43440: Chile, Reina Adelaida Archipelago, Strait of Magellan, west mouth of straits, R/ V Albatross Sta. 2782, 51°12’S, 74°13’30”W, 472 m, 0 6 February 1888, small beam trawl, one colony, 2.5 cm high, in rather poor condition, without gonophores, labelled “ type ”; ethanol. Type locality. Chile: southwest coast, 51°12’S, 74°13’30”W, 472 m (Fraser 1940a). Current status. Invalid. Remarks. The only known name-bearing type material of Diphasia crassa , fixed originally by Fraser (1940a) as the “ type ” and constituting a single colony, is justifiably listed as a holotype in collections at the NMNH (USNM 43440). No specimens assigned to the species exist in the Fraser Hydroid Collection at the RBCM. The coordinates of the station are imprecise as they reflect a location on an island. Fraser (1940a) referred this species, with question, to Diphasia L. Agassiz, 1862. Poorly known and described from infertile material, it was listed under Synthecium Allman, 1872 by Vervoort & Watson (2003). Following the suggestion of Horia R. Galea (personal communication, 31 March 2016), D. crassa is regarded here as a synonym of Synthecium protectum Jäderholm, 1903 (type locality: Cape Valentine, Elephant Island). Of particular note, a distinctive unpaired hydrotheca may occur at the proximal end of each hydrocladium in both D. crassa and S. protectum . Jäderholm (1903) also reported that hydrothecae of S. protectum are partially covered by a flange of the adjoining internode. Published as part of Calder, Dale R. & Choong, Henry H. C., 2018, Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions, pp. 1-83 in Zootaxa 4487 (1) on page 43, DOI:10.11646/zootaxa.4487.1.1, http://zenodo.org/record/1456161